Selection of adaptive strategies in child development through modeling of the Neutrosophic VIKOR method - Gandy Francisco Álvarez Enríquez; Jimmy Fausto Aguirre Solórzano; Jorge Marcelo Thumb Chávez; Odalis Yadira Almeida Huertas (Journal of Fuzzy Extension and Applications)
Comprehensive development in childhood, particularly in primary education, is essential for promoting social, emotional, and cognitive skills. This study aimed to analyze and propose effective strategies that stimulate creativity, social interaction, and emotional well-being during this educational stage. The VIKOR neutrosophic method was utilized to model and select the most effective strategies, considering the criteria of adaptability, autonomy, and comprehensive development. The results indicated that self-directed free play and experiential play strategies, as well as music and movement, were particularly effective during modeling. The first promoted autonomy, creativity, and social skills, while the second enhanced coordination, memory, and emotional expression. In conclusion, both strategies, when adapted to individual needs, have demonstrated a positive impact in school and family environments, providing a solid foundation for future educational policies focused on child well-being.